Exploring the buffalo whey: a look at nanotechnology in search of strategies for the modern nutraceutical industry - Franco E. Vasile (Revista Científica)
Buffalo whey is the most important by-product of the cheese industry. Whey proteins constitute the most exciting component from a technological and economic point of view. They present attractive, functional properties and, similarly to proteins of bovine milk whey, they could also be used as an ingredient (dairy beverages, nutritional supplements) and/or food additives (emulsifier, foaming agent, encapsulant) in novel applications with high-added value, such as nano or microencapsulation. However, buffalo whey has traditionally been used as a raw material for producing ricotta, as animal feed, or well discarded, constituting the main effluent in cheese-making establishments. The use of buffalo whey in novel applications poses a promising scenario, while research is still limited, which warns of endless possibilities.